On the type specimens of Pareas macularius Theobald, 1868 and Pareas berdmorei Theobald, 1868 with the designation of a lectotype for Pareas macularius (Squamata: Serpentes: Pareidae) - David, Patrick; Deuti, Kaushik (Zootaxa, 2022)
In two different publications, William Theobald described, during the same year (1868), two taxa at species level in the snake genus Pareas, namely Pareas macularius and Pareas berdmorei, both based on the same syntypes. However, these two taxa are distinct at species level. We here discuss these descriptions, especially that of P. berdmorei which might have raised a nomenclatural problem. We examined their respective type specimens and we here designate a lectotype for Pareas macularius.